Traditional Accounting vs. Computer Based Accounting: Challenges Faced by Accountants - Hossan, Mohd. Takdir (American Journal of Trade and Policy, 2018)
To face much more difficult and challenging the business world in the challenging professional areas, depth knowledge about any particular filed is very much more compulsory. Accounting is essential function for any commerce and industry. All commerce and industries must keep a record of their revenue and expenses.